Agricultura Familiar, Extensão Rural e Soberania e Segurança Alimentar e Nutricional : delimitando categorias analíticas à luz da implementação do Programa de Aquisição de Alimentos no Brasil - Salgado, Rafael Junior dos Santos Figueiredo (Mundo Agrario.)
The article analyzes the implementation of the Food Acquisition Program (PAA) in Brazil, highlighting its influence on the chain of production and commercialization, obstacles and potentialities for the family agriculture segment. We use qualitative research, outlined as a case study, through direct observation, documentary analysis and semi-structured interviews with family farmers, managers and beneficiary entities. The interviews were submitted to IRAMUTEQ software for lexical content analysis. In addition to representing a unique destination for the surplus produced in the field, the PAA constitutes a relevant public policy instrument, not only for the potential of promoting family farming, but also for promoting food and nutritional security for socioeconomic vulnerability.